Information cosmopolitics an actor-network theory approach to information practices - Tabak, Edin (Waltham, MA Chandos Publishing, 2015)
Information Cosmopolitics explores interaction between nationalist and information sharing practices in academic communities with a view to understanding the potential impacts of these interactions. This book is also a resounding critique of existing theories and methods as well as the launching point for the proposition of an alternate approach. Dominant approaches in the Information Behaviour (IB) field are investigated, as well as questions existing theoretical approaches to nationalism and cosmopolitanism. The concept of information cosmopolitics is introduced as an approach for tracing information practices and enabling research participants to perform their own narratives and positioning, and that the focus of information studies should be on tracing the continuous circulation of processes of individualization and collectivization.
Imprint line also gives Elsevier as a publisher, with multiple offices (Amsterdam, Boston, etc.)
Includes bibliographical references (pages [147]-162) and index.
Keywords: Information behavior -- Sociological aspects; Cosmopolitanism -- Sociological aspects; Nationalism -- Sociological aspects; Information resources -- Sociological aspects